ADAURA: Mature Enough for Publication, Not for Prime Time. (24th December 2020) - Addeo, Alfredo; Banna, Giuseppe Luigi; Friedlaender, Alex
Abstract : This commentary addresses the challenges related to using suboptimal endpoints to justify expedited approval of new drug therapies.